GEOMETRIC DEPENDENCE OF DETERMINING THE MAGNITUDE OF THE INACCURACY OF PENDULUM MECHANISMS - Ekaterina Yu. Churakova, Vokhidov Ayubjon (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article provides an overview of the most popular watch movements that exist today, a kinematic diagram of mechanical pendulum clocks "Mayak", "Yantar" and "OCHZ", as well as calculations of pendulum lengths and periods of their oscillation. The purpose of the article is to investigate the effect of the lengths of pendulums changed by the value from -2 to +2 mm with a step of 0.5 mm on the accuracy of the clockwork. The averaged values ??of the movement of the clockwork per day and their geometric dependence on the adjustment of the length of the pendulum mechanism, which can be used to calculate the adjustment of the lag or advance of the clockwork for a certain period of time, are given. The approximation of these values ??was also carried out and the value of the root-mean-square deviation was determined.